The key to success increasing customer satisfaction of SMEs product souvenir food - Nofrizal; Nurhayani Lubis; Sucherly; Undang Juju; Arizal N; Wita Dwika Listihana (Cogent Business & Management, 2022)
The purpose of this study was to find and test the key success factors for increasing consumer satisfaction in the small and medium industry of souvenir food products in Pekanbaru City, Indonesia by examining the variables of product uniqueness, product completeness, Buying Decision and consumer satisfaction so as to increase business profits. The problem of this study is to find the direct and indirect effects of the variables of product uniqueness, product completeness, Buying Decision and consumer satisfaction of souvenir food products. The population is all consumers who buy food products by the city of Pekanbaru but It is not known the total population. So, the sampling technique uses categories that are not known to the population using the isac k theory with the results of calculations using the formula as many as 173 consumers. sampling technique using proportional sampling. The data used in this study are primary and secondary data using a questionnaire. The measurement scale used is a 5-point Likert scale. The analysis of the data obtained was tested for its reliability validity and hypothesis testing was carried out with Structural Equation Modeling (SEM). The results of the study all factors have a significant influence but on several factors that are not significant, namely the uniqueness of the product on Buying Decision and product completeness on consumer satisfaction through Buying Decision
Keywords: 650; Buying Decision; consumer satisfaction; product completeness; Product uniqueness